The Effects of Angular Velocity and Training Status on the Dynamic Control Equilibrium - Alt, Tobias; Knicker, Axel; Strueder, Heiko (Sports Medicine International Open, 2017)
Thigh muscle imbalances may impair sports performance and cause injuries. Common diagnostic parameters of knee muscle balance lack practical applicability. This cross-sectional study aimed to evaluate the effects of angular velocity and training status on the dynamic control ratio at the equilibrium point representing the intersection of eccentric knee flexion and concentric knee extension moment-angle curves. 58 trained and 58 untrained male participants (22.1 years, 82.4 kg) performed concentric and eccentric knee flexions (prone position) and extensions (supine position) on an isokinetic dynamometer operating at 30 and 150°/s. Trained participants had significantly higher DCRe moments at all angular velocities compared with their untrained counterparts (trained30,150: 1.86, 1.90 Nm/kg; untrained30,150: 1.56, 1.60 Nm/kg; p<0.001, partial η²=0.345). Dynamic control equilibrium moments rose with increasing velocity (p=0.001, partial η²=0.095), whereas dynamic control equilibrium angles (trained30,150: 28.9, 30.8°; untrained30,150: 26.1, 27.0°) were influenced by training status (p=0.004, partial η²=0.072), but not by angular velocity (p=0.241, partial η²=0.012). Dynamic control equilibrium parameters detect thigh muscle balance and reflect the trained participants’ capacity to resist high eccentric knee flexor moments, especially during fast movements. Direct links to muscular loading during sprinting are conceivable, but warrant further investigation. The assessment of dynamic control equilibrium moments and angles might help physiotherapists and coaches to improve functional muscle screening, injury prevention and purposeful return to sport.
Keywords: knee joint; isokinetic dynamometry; muscle strength ratio; hamstring; quadriceps